2011
DOI: 10.1371/journal.ppat.1002263
|View full text |Cite
|
Sign up to set email alerts
|

A Trigger Enzyme in Mycoplasma pneumoniae: Impact of the Glycerophosphodiesterase GlpQ on Virulence and Gene Expression

Abstract: Mycoplasma pneumoniae is a causative agent of atypical pneumonia. The formation of hydrogen peroxide, a product of glycerol metabolism, is essential for host cell cytotoxicity. Phosphatidylcholine is the major carbon source available on lung epithelia, and its utilization requires the cleavage of deacylated phospholipids to glycerol-3-phosphate and choline. M. pneumoniae possesses two potential glycerophosphodiesterases, MPN420 (GlpQ) and MPN566. In this work, the function of these proteins was analyzed by bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 49 publications
7
73
0
Order By: Relevance
“…The formation of a unique tip-like structure comprising a complex of adhesins and adhesion-related proteins was shown to be the basis for effective adherence of bacteria to the respiratory mucosa (Krause & Balish, 2004). The further colonization process is accompanied by the release of hydrogen peroxide (Hames et al, 2009;Schmidl et al, 2011) and of the pertussis toxin-like CARDS toxin (Kannan & Baseman, 2006), resulting in vacuolization and destruction of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a unique tip-like structure comprising a complex of adhesins and adhesion-related proteins was shown to be the basis for effective adherence of bacteria to the respiratory mucosa (Krause & Balish, 2004). The further colonization process is accompanied by the release of hydrogen peroxide (Hames et al, 2009;Schmidl et al, 2011) and of the pertussis toxin-like CARDS toxin (Kannan & Baseman, 2006), resulting in vacuolization and destruction of epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the number of toxins or other toxic compounds produced by mycoplasmas is limited. Among the known exceptions is the capacity of several mycoplasmas to produce hydrogen peroxide (H 2 O 2 ) as a by-product of glycerol metabolism (13,14). For a small number of Mycoplasma species, the secretion of virulence-mediating proteins was demonstrated.…”
mentioning
confidence: 99%
“…We aligned the amino acid sequences of GlpQ (amino acids [aa] 298 to 587, excluding the GPDPase_memb domain) and GlpQ2 (aa 1 to 277) with those of GlpQs from H. influenzae and M. pneumoniae, which showed that residues Glu-46, Asp-48, His-61, and Asp-62 in GlpQ2 and Glu-369, Asp-371, His-384, and His-385 in GlpQ were strictly conserved around the active site of GDPD ( Fig. 1) (16,38). This suggests that both GlpQ and GlpQ2 are biologically active enzymes, although only the glpQ gene is found widely in published S. pneumoniae genome sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxicity assay was modified from that of Schmidl et al (16). A549 cells were cultured to confluence in a 96-well plate without antibiotics and infected with 5 ϫ 10 6 CFU pneumococci for 2 h at 37°C.…”
Section: Ethics Statementmentioning
confidence: 99%
See 1 more Smart Citation